Valoraciones sobre el procesamiento de información en investigaciones asociadas a especialidades médicas - José Carlos Hurtado de la Coba; Belkis Domínguez Cepero; Jesús Oliva Hernández (Centro para el Desarrollo de las Ciencias Sociales y Humanísticas en Salud, 2022)
The present work aims to assess the regularities of the main problems that are evidenced in the use and employment of the dynamics of information processing in research associated with medical specialties, from a selection of theses linked to the specialty of Comprehensive General Medicine and other medical specialties defended in the last 5 years at the University of Medical Sciences of Camagüey. The main results of the documentary review focus on deficiencies in the presentation and interpretation of the nature of the relationships between the variables of the methodological design and the statistical techniques that are used from the design, execution and presentation of the scientific result.